THE 100TH ANNIVERSARY OF GEOLOGICAL SERVICE OF UKRAINE - Pavlyshyn, V.; Vyrshylo, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geological and mineralogical investigations on the modern territory of Ukraine, prior to the establishment of the Ukrainian Geological Committee, were carried out mainly by the Department of Mineralogy (Mineralogy and Geognosy) of Kharkiv, Kiev, Novorossiysk, Lviv University, Yekaterynoslav Higher Mining School, as well as academic institutions, universities and natural communities of Austria-Hungary, Poland and Russia. During World War I geologists began helping the front in Ukraine. They united in the hydro-geological organization "HydroSW" (Hydro-geological Department of the Hydrotechnical Works of the Southwestern Front), as well as in the Division of Raw Materials of the Kiev Military-technical Aid Committee, which became an informal branch of the Petrograd Commission of Raw Materials headed by A.Ye. Fersman. The Regional Geological Council was created on the basis of these organizations after the war. It was headed by V.I. Luchytsky. He considered that since the main direction of the work of the Division of raw materials was geological research, it was logical to preserve and develop this particular direction, giving it the status of a permanent geological institution – the Ukrainian Geological Committee. V.I. Luchytsky prepared a memorandum "On the Establishment of Ukrainian Geological Committee", in which he substantiated the scientific and practical practicability of establishing this institution, primarily for the geological study of the territory of Ukraine, and Committee draft statute. The UGC statute postulates a very important thesis that the Committee will coordinate and consolidate all geological works that will be conducted on the territory of Ukraine. There was the following organizational step: negotiations with the Ministry of Trade and Industry, culminating with the approval UGC statute and staff on February 1, 1918 by the Government. This date marked the beginning of the official history of the Geological Survey of Ukraine in the form of UGC. The first committee was elected at the meeting of the former Department of Raw Materials, which virtually united all the Kiev geologists.
Keywords: Ukrainian Geological Committee; Geological Service of Ukraine; V.I. Luchytsky; B.L. Lychkov; V.V. Reznichenko; V.M. Chyrvynsky